Organizational Culture as determinant of Work Commitment of School Teachers - Imtiaz, Dr. Nasheed (IJRDO- Journal of Educational Research, 2016)
In this modern challenging world, it is quite difficult for organizations to survive.Organizational modernity and work force utilization are becoming increasingly important for anyemerging and growing organization. Hence, among all commitment of an employee is a hallmark for organizations to grow and develop and finally to sustain in the highly competitiveglobal market.To attain maximum possible commitment of employee’s organizations must take care ofthose factors which play significant role in enhancing the commitment level. In view to theabove assertion, organizational culture is one of the very important aspect which plays vital rolefor determining work commitment of employees at work. Hence, present investigation wasundertaken to investigate the determining organizational culture for influencing employees work.The study comprised of N= 200 teachers who were taken from schools. The findings havesuggested that organizational culture significantly influences work commitment.